A study on the influence of dominant sound sources on users’ emotional perception in a pediatric dentistry clinic - Liu, Yang; Chen, Xi (Frontiers in Psychology, 2024)
Introduction Soundscape in dental clinics has varying degrees of impact on the emotions of healthcare workers and young patients. Emotions such as restlessness, anxiety, anger, and nervousness are commonly found among dental healthcare workers. Pediatric dental clinics are an important part of dental clinics, but there is a lack of research on the soundscape within pediatric dental clinics. Methods This study focuses on a typical pediatric dental clinic, using a combination of field questionnaires and objective measurements. It aims to determine the impact of dominant sound sources on the emotional perception (nervousness, restlessness, anger, fear, pain) and hostile emotional responses of users in the pediatric dental clinic. Results In the soundscape of pediatric dental clinics for young pediatric patients, users experience negative emotional perceptions (nervousness, restlessness, anxiety, anger, fear, and pain) and emotional responses of hostility. The dominant sound sources can be divided into two categories: dental (dental drill, air-water syringe, and saliva ejector) and nondental (children crying). Under the influence of dental dominant sound sources, there was a significant negative correlation between the emotional perceptions of healthcare workers and their negative emotional perceptions (p < 0.05). Conversely, for young pediatric patients aged 0–11 years, a significant positive correlation was observed between their emotional perceptions and negative emotional perceptions. The mean perceived degrees of nervousness and fear in young pediatric patients were 1.82 and 1.71 times stronger, respectively, than those observed in healthcare workers. Under the influence of non-dental dominant sound sources, the average degree of emotional perception among healthcare workers was 0.71 higher than that of young pediatric patients, and anxiety perception was significantly enhanced (p < 0.05). The mean degree of nervousness perception was 1 point higher in healthcare workers compared to young pediatric patients, restlessness perception was 1.1 stronger, and there was a presence of mild pain perception. In terms of demographic/social factors, age, occupation, and years of work significantly affected the perceptions of fear and restlessness among healthcare workers, while age had a significant impact on the emotional reaction of hostility in young pediatric patients. Discussion The results of this study indicate that the soundscape is an important factor in creating a comfortable treatment environment in pediatric dental clinics. Healthcare workers and young pediatric patients are significantly affected by the dominant sound sources in the clinic, and these effects are closely related to demographic and social factors such as age, profession, and years of experience. This finding can provide more targeted methods and strategies for the design and creation of soundscapes in dental clinics.